Sex, dementia, capacity and care homes - Bartlett, Peter (Springer, 2010)
This paper addresses the appropriate legal and policy approach to sexual conduct involving people with dementia in care homes, where the mental capacity of one or both partners is compromised. Such conduct is prohibited by sections 34–42 of the Sexual Offences Act 2003, but this article asks whether this blanket prohibition is necessarily the appropriate response. The article considers a variety of alternative responses, eventually arguing that clearer guidance regarding prosecution should be issued.